Toward Equal Educational Opportunity Affirmative Admissions Programs at Law and Medical Schools - Commission on Civil Rights, Washington, DC.; Riedman, Larry; Commission on Civil Rights, Washington, DC. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
Affirmative admissions programs at law and medical schools are examined in the context of the national commitments to equal opportunity and to the eradication of the remaining effects of discrimination. A discussion is presented of the history of past discrimination in education, particularly higher education, and some of its continuing effects, including the underrepresentation of minorities in the legal and medical professions. The traditional admissions process at law and medical schools is examined with respect to both its numerical, objective, or quantitative standards and its subjective or nonquantitative criteria. The problems that gave rise to the need for affirmative admissions programs and the nature and effect of such programs in comparison to traditional admissions programs are reviewed. Appendices present the United States Commission on Civil Rights "Statement on Affirmative Action" and a summary of the position of the Carnegie Council on Policy Studies in Higher Education on "The Relevance of Race in Admissions." (SW)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; Admission Criteria; Admission (School); Affirmative Action; Civil Rights; Equal Education; Higher Education; Law Schools; Medical Schools; Minority Groups; Racial Discrimination; Racial Integration; Reports, Research